2020
DOI: 10.3390/ijgi9030159
|View full text |Cite
|
Sign up to set email alerts
|

Think Spatially With Game Engine

Abstract: Spatial thinking and spatial orientation skills are involved in tasks related to the recognition of landforms, mapping, spatial interpretation, and landscape analysis, and can be developed with specific training. Game engines can facilitate the creation of 3D virtual landforms and provide powerful rendering engines for the graphical representation of landscapes from a first-person perspective. In the present research, 27 engineering students participated in a workshop in a first-person virtual environment usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…Interactivity in current geospatial data visualizations is starting to become available for users to navigate or otherwise work with data to obtain required information and acquire optimal situation awareness [42,43]. In the present paper, the researchers focused on navigational (or viewpoint) interactivity, which was discussed in previous studies [43][44][45][46], and which forms the core functionality of applications such as Google Earth and other virtual globes. Navigational interactivity in 3D space usually includes functions such as rotation, panning and zooming for spatial information acquisition further promoting e.g.…”
Section: Interactivity Factormentioning
confidence: 97%
See 1 more Smart Citation
“…Interactivity in current geospatial data visualizations is starting to become available for users to navigate or otherwise work with data to obtain required information and acquire optimal situation awareness [42,43]. In the present paper, the researchers focused on navigational (or viewpoint) interactivity, which was discussed in previous studies [43][44][45][46], and which forms the core functionality of applications such as Google Earth and other virtual globes. Navigational interactivity in 3D space usually includes functions such as rotation, panning and zooming for spatial information acquisition further promoting e.g.…”
Section: Interactivity Factormentioning
confidence: 97%
“…Navigational interactivity in 3D space usually includes functions such as rotation, panning and zooming for spatial information acquisition further promoting e.g. spatial orientation [46]. Previous studies [19,45,[47][48][49] suggested a difference between static and interactive scenes in perception and cognitive processes, and respectively emphasized the importance of the specific task type [45].…”
Section: Interactivity Factormentioning
confidence: 99%
“…Penulis juga tertarik dengan quiz online seperti Socrative, Kahoot, Quizlet Live, Mentimeter, Poll Everywhere atau Plickers [3]. Pembuatan game akan dibuat dengan menggunakan game engine unity, dimana unity menawarkan fleksibelitas dalam merancang game dan simulasi-simulasi pada berbagai bidang [4].…”
Section: Pendahuluanunclassified
“…Review on the utilization of the game engines for terrain rendering using geospatial data also highlights the importance and potential of the research topic 12,30 . Game engines can facilitate the creation of 3D landscapes and provide powerful rendering engines for the graphical representation of landscapes 31 . Recently, the idea of unity game engine extension for interactive visualization of point clouds data proved fruitful 10 .…”
Section: Related Workmentioning
confidence: 99%